(untitled) (Journal of Universal Science Research, 2025)
This article explores the structural and semantic characteristics of proverbs in Jane Austen’s novels. It examines how Austen’s proverbs reflect social norms, psychological insights, and cultural values. Through syntactic and semantic analysis, the study categorizes these proverbs into simple, compound, and complex sentences, highlighting their linguistic functions. The research contributes to the field of paremiology and literary linguistics by analyzing how Austen’s proverbs shape character development and narrative structure. The study integrates perspectives from scholars like W.Mieder, R.Firth, and B.Jurayeva to provide a broader understanding of proverbial expressions in literature.